KOMPENSASI DAN LINGKUNGAN KERJA SERTA PENGARUHNYA TERHADAP KOMITMEN ORGANISASI - Arif Rachman Putra; Rahayu Mardikaningsih (JURNAL ILMIAH EDUNOMIKA, 2021)
Organizational commitment becomes an important variable to determine employees work more effectively and deliver results according to organizational expectations. Organizations with low organizational commitment of employees will only hamper the achievement of organizational goals because efforts to develop organizational commitment are closely related to improving employee performance. This causes the study of organizational commitment and the variables that influence it is still relevant and important to be analyzed further in order to make a meaningful contribution to the development and dynamics of the organization. Of the many variables that can influence organizational commitment, compensation and work environment variables are still considered relevant to be observed based on the dynamics of current organizational behavior in each organization. This study aims to analyze the effect of compensation and work environment on organizational commitment of employees. In this study the sampling method was carried out randomly and involved 59 respondents. Multiple linear regression analysis using SPSS 25 for Windows software is used as an analysis and data processing tool. The results showed compensation and the work environment had a significant effect on employee organizational commitment partially and simultaneously. Keywords : Compensation, work environment, wages, human resources, organizational commitment